Adzina : An Indigenous System of Trial by Jury on the Ghana-Togo Border - World Bank (Washington, DC, 2012)
In a recent article in this series, the author discussed the indigenous principles that undergird the maintenance of social control among Buems of Buem-Kator on the Ghana side of the Ghana-Togo border in the Buem Traditional Area in the Jasikan District in the Volta Region of Ghana. The current article, too, is about the same Buems. In this one, the author presents the indigenous Buem jury system, known as adzina. But before discussing the nature and process of adzina, he first discusses bate kate, which is the Buem forum for adjudication of which adzina is an integral part. According to the Buem elders, Buems make it a point to try to avoid bate kate which they consider to be adversarial and time-consuming, not only to the disputants, but also to their respective kinsfolk who are customarily obliged to accompany them to hearings. Unlike benyaogba ukpikator-discussed in the article earlier mentioned -bate kate is a more elaborate process, which proceeds in stages and normally involves intensive cross-examination and assembling of witnesses and, where necessary, exhibits. In terms of monetary outlay too, bate kate can be expensive. This is because fines, and in some cases, costs are imposed on convicted parties.